2014
DOI: 10.1007/s10995-014-1615-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Pregnancy Intendedness Across U.S. Women’s Pregnancies

Abstract: How stable are women's pregnancy intentions across their reproductive lifespans? Are there demographic, social, or attitudinal characteristics that are associated with differing pregnancy intentions patterns? Patterns of intendedness across pregnancies were examined using a sample of 3,110 women ages 25-45 who have been pregnant at least twice from the National Survey of Fertility Barriers. Multinomial logistic regression analyses assessed associations between patterns of intentions and respondents' economic/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…In terms of associated factors, unintended pregnancy in this sample was predominantly more likely with younger age, brown and yellow skin color, lower schooling level, not having a partner, not having a paid job, alcohol abuse and tobacco use. The effect of sociodemographic and individual variables is consistent with literature on intention of pregnancy at conception and showed the high degree of social vulnerability of these women [ 19 , 20 ]. Prietsch and colleagues [ 18 ], investigating the factors associated with unplanned pregnancy in a sample of women in Southern Brazil, found statistically significant association between having an unplanned pregnancy and having black and brown skin color, being a teenager, being single, having a low income, being a smoker and having multiparity.…”
Section: Discussionsupporting
confidence: 86%
“…In terms of associated factors, unintended pregnancy in this sample was predominantly more likely with younger age, brown and yellow skin color, lower schooling level, not having a partner, not having a paid job, alcohol abuse and tobacco use. The effect of sociodemographic and individual variables is consistent with literature on intention of pregnancy at conception and showed the high degree of social vulnerability of these women [ 19 , 20 ]. Prietsch and colleagues [ 18 ], investigating the factors associated with unplanned pregnancy in a sample of women in Southern Brazil, found statistically significant association between having an unplanned pregnancy and having black and brown skin color, being a teenager, being single, having a low income, being a smoker and having multiparity.…”
Section: Discussionsupporting
confidence: 86%
“…However, given the complex emotional, psychological, and cultural factors at play, often behaviors do not align with intentions (10, 14, 2426), and intentions may change over time (2729). Indeed many women express ambivalence regarding their pregnancy intentions (3033), and formulating plans for a pregnancy may seem unrealistic for many women as they do not perceive themselves as having reproductive control (34).…”
Section: Introductionmentioning
confidence: 99%
“…When Shreffler et al retrospectively examined intentions across individual women's pregnancies, they found that 60% of women did not report the same intention for all pregnancies (Shreffler, Greil, Mitchell, & McQuillan, 2015). Morgan examined fertility intentions stratified by age and parity across several data sources, and his findings suggested that uncertain fertility intentions represent a transitional stage from childbearing to post-childbearing, (Morgan, 1982).…”
Section: Introductionmentioning
confidence: 99%